2019
DOI: 10.3389/fneur.2019.01293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ulinastatin Combined With Dexmedetomidine on Postoperative Cognitive Dysfunction in Patients Who Underwent Cardiac Surgery

Abstract: Background: Recent studies have shown that early diagnosis and intervention promote the patient's good prognosis. For patients who underwent cardiac surgery and require extracorporeal circulation support, the incidence of postoperative cognitive dysfunction (POCD) is higher than in other types of surgery due to greater changes in brain perfusion compared with normal physiological conditions. Recent studies have confirmed that the use of ulinastatin or dexmedetomidine in the perioperative period effectively red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(71 citation statements)
references
References 20 publications
0
68
1
1
Order By: Relevance
“…POCD was diagnosed by Z-score in a comprehensive test scale recommended by the International Study of POCD (ISPOCD) [14]. Patients were de ned as having POCD when Z-score were above 1.96 using cross-reference [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…POCD was diagnosed by Z-score in a comprehensive test scale recommended by the International Study of POCD (ISPOCD) [14]. Patients were de ned as having POCD when Z-score were above 1.96 using cross-reference [15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we combined neurocognitive score and IL-6 simultaneously. We used the recommended tests by ISPOCD in the present study and calculated Z-score above 1.96 to diagnose POCD [15]. This method avoided oor or ceiling effects.…”
Section: Discussionmentioning
confidence: 99%
“…Specific to our study design, four studies concentrated on cardiac valve surgery ( 24 , 26 , 28 , 34 ), 15 studies included combined CABG and valve surgeries ( 10 , 16 23 , 25 , 27 , 29 , 31 , 33 , 37 ), and the remaining five studies related to CABG ( 15 , 30 , 32 , 35 , 36 ). Dexmedetomidine was administered during the intraoperative period in six studies ( 26 – 29 , 31 , 35 ), the perioperative period in eight studies ( 10 , 15 , 23 25 , 33 , 34 , 37 ), and the other 10 studies during the postoperative period ( 16 22 , 30 , 32 , 36 ). CAM/CAM-ICU was used in nine studies as the diagnostic tool for POD ( 16 , 18 , 20 , 23 , 25 , 30 33 ) and five studies used RASS ( 10 , 17 , 19 , 21 , 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dexmedetomidine is an α 2 -adrenoreceptor agonist that calms, reduces pain, and inhibits the activity of the sympathetic nervous system, but also can inhibit the in ammatory response and stress response, reduce neuronal toxicity and apoptosis, and promote brain protection through synapse formation and neurotrophic nutrition 30 . Zeng and colleagues showed that dexmedetomidine can affect expression of proin ammatory factors and reduce the in ammatory response in blood vessels by activating the corresponding signaling pathways 31 .…”
Section: Discussionmentioning
confidence: 99%